SIHIR RACUN SANGGA DALAM KHAZANAH BUDAYA BANJAR: DIALEKTIKA ANTARA MISTIK TRADISIONAL, HUKUM ISLAM, DAN HUKUM PIDANA NASIONAL - Masrudi Muchtar; Aulia Muthiah (Yayasan Pendidikan Literasi Borneo, 2025)
Sihir Racun Sangga is understood as part of a spiritual heritage that has been part of people's daily lives for centuries. In this context, poison is not merely a criminal practice, but also a symbol of a belief system that encompasses an understanding of metaphysical powers, human relationships, and a local conception of justice. Sihir Racun Sangga is known to have the ability to access supernatural powers to harm or influence others, usually for emotional reasons, personal conflicts, or even power struggles. It is the power of poison magic that the author examines from the perspective of Islamic law and criminal law. The research method used by the author is normative research, with a statute approach and a conceptual approach. This approach was chosen because this study seeks to examine based on a criminal law and Islamic law approach. This research concludes that Islamic law strictly prohibits all forms of sorcery because it contradicts the principle of monotheism and endangers social life. In national criminal law, particularly the new Criminal Code (Law No. 1 of 2023), acts of sorcery or black magic have been criminalized in Article 252, but its regulation still leaves implementation problems, particularly related to evidence, the potential criminalization of local beliefs, and the lack of a cultural-based approach in assessing such cases.